Use of biologics in chronic sinusitis with nasal polyps. Issue 4 (August 2019) - Wang, Chengshuo; Zhang, Luo
Abstract : Purpose of review: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a heterogeneous inflammatory condition with different endotypes between patients from eastern or western countries. Targeted biologics are currently used to treat CRSwNP, but the outcomes widely vary. This review focuses on the present use of biologics for treating CRSwNP. Recent findings: Monoclonal biologics have been used as an innovative therapy for multiple allergic diseases and comorbid allergic conditions. Over the past several decades, numerous biomarkers have been investigated and were found to be closely correlated with CRSwNP, improving the understanding of inflammatory patterns and endotype classifications for CRSwNP and prompting discussion regarding the use of biologics in CRSwNP. Efficacies vary in reports of different research groups, but it has been found that patients with TH-2-driven inflammatory patterns respond better to the use of biologics than those with non-TH-2-driven CRSwNP. These findings suggest the importance and urgency of developing criteria for biologics in CRSwNP. Summary: Precisely determining patient criteria, identifying treatment biomarkers based on endotyping for CRSwNP and determinations of contraindications for long-term utilization may be useful for optimizing treatment strategies and improving the therapeutic efficacy of biologics to achieve long-term control starting at early stages.